2017
DOI: 10.1002/lom3.10171
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of dissolved organic phosphorus using electrodialysis‐reverse osmosis and solution 31P‐NMR

Abstract: The composition of dissolved organic phosphorus (DOP), which directly impacts its biological and chemical reactivity, remains poorly constrained due to methodological and operational challenges. A series of compound‐specific isolation experiments and bulk estuarine seawater isolations were conducted to assess the ability of coupled electrodialysis (ED) and reverse osmosis (RO) to isolate DOP from seawater for molecular characterization using solution 31P‐NMR analysis. These isolations were carried out using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…One caveat is that monoP may not be as efficiently recovered using the ED/RO technique relative to diP. While our isolation results indicated almost complete recovery and characterization of the entire DOP pool (Table 1), Bell et al (2017) found a significant relationship between isolation recovery and MW. Smaller compounds, such as phosphomethyl-glycine (MW = 169), were recovered with 50% efficiency while larger compounds, such as RNA (assumed MW = 3360), were recovered near 80%.…”
Section: Phosphoestersmentioning
confidence: 62%
See 3 more Smart Citations
“…One caveat is that monoP may not be as efficiently recovered using the ED/RO technique relative to diP. While our isolation results indicated almost complete recovery and characterization of the entire DOP pool (Table 1), Bell et al (2017) found a significant relationship between isolation recovery and MW. Smaller compounds, such as phosphomethyl-glycine (MW = 169), were recovered with 50% efficiency while larger compounds, such as RNA (assumed MW = 3360), were recovered near 80%.…”
Section: Phosphoestersmentioning
confidence: 62%
“…Similar to low MW monoP compounds, pyroP may also have been under-recovered. Yet, it is also possible that alkaline dissolution impacted our results by degrading polyP (Bell et al 2017), although Turner et al (2003) found their polyP standard to be stable for 9 d in NaOH-EDTA. Terminal P from di-and triphosphate mononucleotides could also be included in the pyroP signal, although this would result in an ester bonded P peak (i.e., nucleoP α ) between −9 and −11 ppm (Figs.…”
Section: Phosphoanhydridesmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, the forms and concentrations of P in algae shall be evaluated while algae debris is decomposing. However, until now, studies of the species, concentrations, and effects of P o in algae of eutrophic lakes have been limited because of the complexity and limitations of analytical methods (Turner et al 2005;Bell et al 2017).…”
Section: Introductionmentioning
confidence: 99%